Nanoenergetic material-on-multiwalled carbon nanotubes paper chip as compact and flexible igniter. (April 2017) - Kim, Kyung Ju; Jung, Hun; Kim, Ji Hoon; Jang, Nam Soo; Kim, Jong Man; Kim, Soo Hyung
Abstract: A compact and flexible multiwalled carbon nanotubes (MWCNTs)-coated paper electrode was fabricated in this study. The shape of the paper electrode could be varied simply by cutting it. Further, its electrical resistance did not change appreciably either when it was bent with different curvatures or when it was subjected to repeated bending and stretching. An nanoscale energetic material (nEM)-on-MWCNTs paper chip formed by depositing an nEM thin film on the MWCNTs-coated paper electrode could be stably ignited by applying voltages higher than ∼ 15 V. The ignition and explosion characteristics of the chip were investigated systematically. It was found that the explosion reactivity of the chip increased with an increase in the thickness of the nEM thin film. Finally, the remote ignition of the nEM-on-MWCNTs paper chip was successfully demonstrated by explosively breaching a door, suggesting that such nEM-on-MWCNTs paper chips can be used as compact, flexible, and versatile igniters in various civil and military applications. Graphical abstract: